MATERIAL LOKAL SEBAGAI PERWUJUDAN NILAI VERNAKULAR PADA RUMAH BALAI SUKU DAYAK BUKIT - Naimatul Aufa (INFO-TEKNIK, 2009)
In the Southern Kalimantan lies the mountainous range which is calledMeratusMountain. In this mountain, there live Dayak Meratus tribe or more common with the name of Dayak Bukit tribe. The Dayak Bukit tribe has a traditional house named Rumah Balai. At present Rumah Balai has abandoned the heritage values that given from the ancestors.The traditional houses have vernacular values however if the tradition values has been abandoned has it still the vernacular values? To answer this problem this study analyzes the vernacular values of Rumah Balai with the limitation on the local material as the realization of vernacular values toward the traditional Rumah Balai of Dayak Bukit tribe.This study formulates turner’s theory (2002) about the establishment of vernacular architecture to find out the concept of local material as the realization of vernacular values of Rumah Balai of Dayak Bukit tribe as well as how is the implementation of local material as the realization of vernacular values in Rumah Balai of that Dayak Bukit tribe.By applying the qualitative rationalistic can be found that the concept of local material in Rumah Balai of Dayak Bukit tribe includes the sacred values because there are rules and norm. Meanwhile the implementation of local material as vernacular values is since on the structure and construction system as the result of local knowledge of Dayak Bukit tribe.